AUTHENTIC HAPPINESS AS A MEDIATOR OF LEARNING ORGANIZATION AND AUTHENTIC PERSONAL BRANDING ON WORK ACHIEVEMENT - Shanti, Indira; Robinson Manurung, Antonius Dieben (Dinasti Publisher, 2020)
This study aims to analyze the effect of learning organizations and authentic personal branding on work achievement with authentic happiness as a mediator. Considering work achievement must be used as a goal to motivate employees in order to prepare themselves to enter the era of society 5.0. Data analysis techniques were carried out using structural equation model. The results of this study indicate that; (1) there is a positive and significant influence on authentic happiness on work achievement; (2) there is a positive and significant influence of learning organizations on authentic happiness; (3) there is a positive and significant influence on authentic personal branding on authentic happiness; (4) there is a positive and significant influence of learning organizations on work achievement with authentic happiness as a mediator; and (5) there is a positive and significant influence on authentic personal branding on work achievement with authentic happiness as a mediator.